A phylogenetically distant clade of Nostoc–like (Cyanobacteria) taxa with the description of Reofilinostoc matlalcueyense gen. et sp. nov. from an extreme environment - Garduño-Solórzano, Gloria; Martínez-García, Martha; Scotta Hentschke, Guilherme; Miguel Solorza, Luis Fernando; Vasconcelos, Vitor M. (Phytotaxa, 2024)
Although species of the order Nostocales have morphological similarities to each other, some Nostoc species have been considered cryptic and are classified in the families Nostocaceae, Nodulariaceae and Aphanizomenaceae. Since then, the phylogenetic and morphological evaluation of Nostoc-like organisms has led to the taxonomic revision of some genera in different families. In the present work a cyanobacterium morphologically identified as Nostoc was isolated from an extreme cold lotic environment, in a high mountain of the Transmexican Volcanic Belt, and was taxonomically and phylogenetically characterized based on a polyphasic approach. Analysis of the 16S rRNA gene sequence references: Reofilinostoc matlalcueyense gen. et sp. nov. Thus, establishing a new genus of the family Nodulariaceae. The morphology of Reofilinostoc in the wild is reminiscent of a mouse ear, it is of 0.4-1.2 cm in length and has a firm cartilaginous texture; colonies can be pale green, brown or dark green in colour. Through a microscopic inspection, the filaments resemble to Komarekiella atlantica, Desikacharya nostocoides and Minunostoc cylindricum. While, the phylogenetic approach yielded similar results and consistently showed that Reofilinostoc matlalcueyense F02 (OR724089) is closely related to D. nostocoides and M. cylindricum in the core clade of Nodulariaceae. This research revealed that some comparisons between genera of Nodulariaceae exhibited similarity values higher than 97%, such as Atlanticothrix vs. Goleter and Cyanocohniella vs. Anabaenopsis. Nevertheless, in comparison to these phylogenetically closer genera, a substantial difference in the length and structure of D1-D1’, Box-B and V3 helix was demostrated; where Reofilinostoc, Desikacharya, and Minunostoc are part of the Nodulariaceae family; leading to the establishment of Reofilinostoc gen. nov., with Reofilinostoc matlalcueyense sp. nov. as the type species.